Effect of CO2 content, reservoir temperature and pressure of SACW on oil recovery - Junin, Radzuan (SIC, 2016)
The oil recovery can be enhanced by surfactant alternating carbonated water (SACW) injection which is considered a new tertiary recovery method. Carbone dioxide (CO2) concentration, injection pressure and temperature may have a significant effect on the oil recovery factor. Sand pack core flooding experiments were performed in this research. Glass beads were compacted into stainless steel tube ( 34.5 cm length and 3.8 cm diameter ). The synthesis brine water and crude oil saturated the sand pack and aged for 4 days to established real oil reservoir conditions at reservoir temperature , pressure and NaCl salinity of 30,000 ppm . In addition, Sodium dodecly sulfate (SDS) surfactant solution was used for surfactant flooding. The effectiveness of three parameters on the recovery factor have been studied by applying SACW. Firstly, different carbonation levels of CO 2 in brine water injection such as 100%, 50% and 0.0%. Secondly, different injection pressures including 1500, 2100 and 2750 psi. Finally, different reservoir temperatures of 40C, 50C and 60C. The procured results revealed that oil recovery factor substantially affected by these parameters. It exhibited a markedly increase in the recovery factor as a result of CO2 concentration in brine water injection increases. Furthermore, higher injection pressure illustrated higher recovery factor. Similarly, the higher reservoir temperature depicted a significant increase in the recovery factor. Consequently, more oil production rate may be attributed to reservoir temperature and pressure due to CO2 concentration.